The Effects of Self-efficacy, Personal Innovativeness and Career Related Learning of Individuals who experienced Change Jobs on Smart Learning Continuous Usage Intention - Jinhyuk Kwon; Ahreum Hong (International Journal of Psychosocial Rehabilitation, 2020)
With the transformation of the entire industry through digital transformation, the birth of new jobs and the disappearance of existing jobs are foreseen. Labor market is expected to become more flexible in the future, and the demand for individual-level learning for turnover and career management, which is a transition to new jobs, is expected to increase. In modern society, the disappearance of lifelong work and a positive change in the perspective on workplace movements, as well as the volatility and uncertainty in the social environment, have increased the number of workers who are learning to respond more actively to the unpredictable future. Learning can be described as career learning, a formal and informal activity that is self-directed, planned, active, and ongoing for your own future and future career development. Based on the expanded skill acceptance model, this study examines how the individual characteristics of the employee's self-efficacy and personal innovation affect the perceived usefulness and perceived usability, and the perceived usefulness and perceived ease of use. This study examined how it affects the continuous use of smart learning. The subjects of this study were 20-30 employees who experienced turnover, who experienced smart learning during the turnover process, and analyzed the frequency of surveys using the STATA / SE 12.0 program to analyze 332questionnaires. , Reliability analysis, descriptive statistical analysis, etc., and empirical analysis through Structural Equation Modeling (SEM). The research results from hypotheses, analysis and verification are as follows. First, self-efficacy for smart learning has a significant effect on perceived usefulness and perceived usability. In other words, the higher the self-efficacy, the more statistically significant influence on the significance and ease of use. Second, personal innovation for smart learning has a significant effect on perceived usability, but does not have a significant effect on perceived usability. Third, perceived usefulness did not have a significant effect on career learning, but perceived usability had a significant effect on career learning. Fourth, career learning did not have a significant effect on the continuous use intention of smart learning. Fifth, perceived usefulness and perceived ease of use had a significant effect on sustained use intention. For learners who have a strong self-directed learning tendency, such as turnover, self-efficacy and personal innovation, which are personal characteristics, are important to the continuous use of smart learning and affect career learning. This study considers the differences according to the inclination and characteristics when establishing the learning strategy considering the inclination and characteristics of the learners, establishes the learning and career learning plan and the human resource development plan, designs the education service according to the characteristics of the users, and learns. It can be used to formulate a strategy.